Transshipment Hub Port Competitiveness of the Port of Colombo against the Major Southeast Asian Hub Ports* - Chathumi Ayanthi Kavirathna; Tomoya Kawasaki; Shinya Hanaoka (Asian Journal of Shipping and Logistics, 2018)
The hub port competition has intensified beyond regional boundaries, resulting in the port of Colombo competing with the Southeast Asian hub ports of Singapore, Klang, and Tanjung Pelepas in the transshipment market. This study analyzes the competitiveness of Colombo as a transshipment hub in “hub and spoke” and “relay” networks. Shipping lines evaluate the selection criteria for transshipment hub ports and the performance of competitive hub ports. The generalized cost approach together with a discrete choice model is used to assess port choice behavior by estimating the transshipment market share of hub ports and analyzing several scenarios. The results reveal Colombo's lack of competitiveness in relay networks and most of the feeder ports in hub and spoke networks, mainly due to its high deviation from trunk sea routes and lower performance in some non-quantitative criteria. Singapore has dominant market share in relay networks and for most feeder ports in hub and spoke networks, mainly due to its high performance in non-quantitative criteria, except Pipavav and Nhava Sheva, dominated by Colombo. Keywords: Transshipments, Generalized Cost, Hub and Spoke, Relay, Port of Colombo